Pendidikan Tasawuf Perspektif Buya Hamka - Moh Faishol; Hanifuddin . (UMSU, 2019)
The purpose of this research is to describe the concept of Sufism education proposed by Buya Hamka. This research uses intellectual biographical approaches beside philosophical approaches, with the type of library research and using qualitative methods.The method of data collection used is by collecting various works produced by the figures studied (as primary sources), namely: 1) Modern Sufism. 2) Development and Purification of Sufism. 3) Sufism Contemplation. 4) Interpretation of Al- Azhar 5) Memories of Life. And searching for various essays by others about Sufism and Hamka's thinking. Data analysis is done in three steps, namely data reduction, data presentation; and drawing conclusions. While the analysis techniques used are content analysis and interpretation. The results of the study indicate that: First, the concept of Hamka Sufism is very moderate when compared to Sufism concepts from most Sufis, especially in Indonesia. And the pattern of Hamka Sufism is categorized in two patterns, 1) patterned Sunni Sufism, and 2) patterned akhlaqi Sufism. Second, Sufism in Hamka's perspective is categorized as traditional or conventional education, that is by good example (uswah hasanah), or modeling, practice and habituation, with auto-motivation or cultivating motivation and self-awareness to worship God and the best things.